Metoprolol for prophylaxis of postoperative atrial fibrillation in cardiac surgery patients: systematic review and meta-analysis - Mohd, Noor Norhayati; Ismail, Saiful Bahari; Zaharah, Sulaiman; Hussain, Nik Hazlina Nik; Zainuddin, Mohammad Aimanazrul; Muhammad, Irfan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2020)
Purpose Postoperative atrial fibrillation (POAF) is a potentially lethal and morbid complication after open heart surgery. This systematic review and meta-analysis aimed to investigate metoprolol compared with other treatments for prophylaxis against POAF. Methods We searched CENTRAL, MEDLINE, EMBASE and trial registries for randomised controlled trials that evaluated metoprolol for preventing the occurrence of POAF after surgery against other treatments or placebo. Random-effects model was used for estimating the risk ratios (RRs) and mean differences with 95% CIs. Results Nine trials involving 1570 patients showed metoprolol reduced POAF compared with placebo (416 patients; RR 0.46, 95% CI 0.33 to 0.66; I²=21%; risk difference (RD) –0.19, 95% CI –0.28 to –0.10). However, metoprolol increased the risk of POAF compared with carvedilol (159 patients; RR 1.59, 95% CI 1.20 to 2.12; I²=4%; RD 0.13, 95% CI 0.06 to 0.20). There was no difference when compared with sotalol or amiodarone. The occurrence of cardiovascular conditions after drugs administration or death between the groups was not different. The overall quality of evidence was moderate to high. Subgroup analysis and funnel plot were not performed. Conclusions Metoprolol is effective in preventing POAF compared with placebo and showed no difference with class III antiarrhythmic drugs. Death and thromboembolism are associated with open heart surgery, but not significant in relation to the use of metoprolol.